Learners’ Satisfaction towards Online Chinese Phonetics Lessons on JFK Online Courses - Silwattananusarn, Tipawan; Watthanawelu, Nareerat; Piyakan, Piyawan (Journal of Information and Learning [JIL], 2020)
The purpose of this research was to examine learners’ satisfaction towards three sets of Chinese phonetics lessons (Pinyin) i.e., single vowels and consonants, diphthongs and special vowels, and nasal vowels, on JFK online course system. The sample was comprised of 93 undergraduate students from Prince of Songkla University, Pattani Campus enrolled in the second semester of academic year 2017, and other learners. A questionnaire was used for data collection. Statistics used in the research were percentage, mean, and standard deviation. Research findings revealed that the learners were satisfied with the three sets of the Chinese phonetics lessons (Pinyin) in maximum level. The lesson set that has the highest average satisfaction is single vowels and consonants, followed by diphthongs and special vowels, and nasal vowels, respectively. They were most satisfied with the five main elements of the lesson format including learning outcomes, content structure design, learning activities design, teaching and learning materials, and applications.